Trained athletes and cognitive function: a systematic review and meta-analysis - Logan, N. E.; Henry, D. A.; Hillman, C. H.; Kramer, A. F. (International Journal of Sport and Exercise Psychology, 2022)
As trends in physical inactivity continue to increase throughout the lifespan, one prominent area of interest is the cumulative benefits of participating in physical activity. Recent literature has demonstrated the cognitive and brain benefits associated with one such population, elite athletes. However, it is unclear which aspects of the athlete experience drive this athlete-cognition relationship, which is the objective of the current study. In this study, we examine, in a quantitative meta-analysis (k = 41), the relationship between athlete experiences and laboratory-based measures of cognitive function in the following domains: attentional allocation, inhibitory control and cognitive flexibility. Athlete groups outperform control groups on a battery of cognitive tasks, including attentional allocation (g = 1.18) and cognitive flexibility (g = 0.31). Moreover, athlete type and experience are important factors to consider when evaluating this relationship. Moderator analyses revealed that athletes trained in aerobic (g = 0.93) or HIIT team-based sports (g = 0.65), as well as child (g = 0.26), elite (g = 0.94) (semi-professional, professional, national and international) or older adult athletes (g = 0.91) were responsible for driving this effect. At a time when physical inactivity levels are increasing, these results have important societal considerations. Participating in sport-related physical activity may be a beneficial influence on cognitive development throughout the lifespan.